Xanthohumol Induces ROS through NADPH Oxidase, Causes Cell Cycle Arrest and Apoptosis. (10th November 2021) - Wang, Chun-Ming; Chen, Jun; Zhao, Jing; Hu, Shan-Shan; Zhang, Shu-Qiu; Mi, Xiang-Quan; Shi, Xiang; Cao, Xin-Hui; Li, Zhen
Abstract : Reactive oxygen species (ROS) are either toxic in excess or essential for redox signalling at the physiological level, which is closely related to the site of generation. Xanthohumol (XN) is an important natural product of hops ( Humulus lupulus L.) and was reported to induce ROS in mitochondria. While in the present study, our data indicate that NADPH oxidase (NOX) is another site. In human acute myeloid leukemia HL-60 cells, we first identified that cell proliferation was inhibited by XN without affecting viability, and this could be alleviated by the antioxidant N-acetyl-L-cysteine (NAC); cell cycles were blocked at G1 phase, apoptosis was induced in a dose-dependent manner, and malondialdehyde (MDA) content was upregulated. XN-induced ROS generation was detected by flow cytometry, which can be inhibited by diphenyleneiodonium chloride (DPI, a NOX inhibitor), while not by N G -methyl-L-arginine acetate (L-NMMA, a nitric oxide synthase inhibitor). The involvement of NOX in XN-induced ROS generation was further evaluated: immunofluorescence assay indicated subunits assembled in the membrane, and gp91 phox knockdown with siRNA decreased XN-induced ROS. Human red blood cells (with NOX, without mitochondria) were further selected as a cell model, and the XN-induced ROS and DPI inhibiting effects were found again. In conclusion, our results indicate that XN exhibits antiproliferation effects through ROS-related mechanisms, and NOX is a source of XN-induced ROS. As NOX-sourced ROS are critical for phagocytosis, our findings may contribute to the anti-infection and anti-inflammatory effect of XN.